Bahasa Inggris - Ramadhanu, Yoga; Lovelly Dwinda Dahen; Jimi Ronald (Global Action and Education for Society, 2025)
This study aims to determine 1) the effect of critical thinking skills on academic achievement, 2) the effect of critical thinking skills through learning interest as an intervening variable on academic achievement, 3) the effect of learning independence on academic achievement, 4) the effect of learning independence through learning interest as an intervening variable on academic achievement, 5) the effect of family environment on academic achievement, 6) the effect of family environment through learning interest as an intervening variable on academic achievement, 7) the effect of learning facilities on academic achievement, 8) the effect of learning facilities through learning interest as an intervening variable on academic achievement, and 9) the effect of learning interest on academic achievement. The research was conducted in July 2025. This research is associative in nature. The population in this study consists of 324 eighth-grade students at SMP N 1 Lubuk Sikaping. Sampling was conducted using proportional random sampling with a sample size of 175 people. The data analysis techniques used were descriptive analysis and path analysis, with the assistance of Eviews 8 and SPSS version 20.0. The research results showed that: 1) there is a positive and significant effect of critical thinking ability on academic achievement, with a path coefficient value of 0.340 and a t-value of 10.882 > t-table 1.653. 2). There is a negative and significant influence of learning independence on academic achievement, with a path coefficient of -0.347 and a t-value of -9.847 > t-table 1.653. 3). There is a negative and significant effect of family environment on academic achievement, with a path coefficient of -0.161 and a t-value of -4.841 > t-table 1.653. 4). The negative and significant effect of learning facilities on academic achievement, with a path coefficient value of -0.117 and a t-value of 3.273 > t-table 1.653. 5). The negative and significant effect of learning interest on academic achievement, with a path coefficient value of -0.582 and a t-value of -16.141 > t-table 1.653. 6). The positive and significant effect of critical thinking ability on learning interest with a path coefficient value of 0.129 and a t-value of 1.958 > t-table 1.653. 7). The positive and significant effect of learning independence on learning interest with a path coefficient value of 0.268 and a t-value of 3.722 > t-table 1.653. 8). The positive and significant effect of family environment on learning interest with a path coefficient value of 0.154 and a t-value of 2.213 > t-table 1.653. 9). The positive and significant effect of learning facilities on learning interest with a path coefficient value of 0.239 and a t-value of 3.242 > t-table 1.653.